The impact of boxing training on the physical condition of first-year students - Chuzhinov A.O.; Timofeeva O.V.; Lubyshev E.A.; Fadina O.O. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to empirically assess the impact of boxing-specific training on the physical fitness of first-year students. Methods and structure of the study. The educational experiment was carried out at the Patrice Lumumba Peoples’ Friendship University of Russia over the course of one academic year. The participants were first-year students from the Faculty of Physics, Mathematics, and Natural Sciences, with a total of 450 students. At the start of the academic year, we formed two groups: an experimental group and a control group. Each group consisted of 20 students, for a total of 40 students. We used a questionnaire to select the participants for the experiment. The experimental group focused on boxing. They learned the basic punches of a boxer and incorporated blocking techniques to enhance their special and general physical fitness. At the end of the academic year, we organized boxing competitions to determine the winners among the students in the experimental group. Meanwhile, the control group followed the general physical training program. Results and conclusions. At the end of the experiment, more significant reliable changes in the level of physical fitness were obtained in the students of the experimental group (boxing). Based on the results obtained, it can be stated that classes in the experimental group using the boxing specialization more effectively affect the level of physical fitness of male students.